SEJARAH PERADABAN ISLAM DI CINA DAN NILAI-NILAI PENDIDIKAN ISLAM DALAM NOVEL ASSALAMUALAIKUM BEIJING - Widada, Dwi Masdi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The phrase that describes that a science should be pursued even to China. Novel Assalamualaikum Beijing provides an overview of the presence of Islam in the Bamboo Curtain country. Islamic civilization has appeared some time ago in China. The novel is intentionally prove that Islam was, and triumphed in China. Islam not only had triumphed in Europe, especially Andalusia (now Spain). Travelling around the main character of China as a columnist Asma Indonesia provided a glimmer of hope, strength, and love of the teachings of Islam. Islam never lived and interacted with the people of China. Chinese Muslim faces with hoods and eyes sipitnya show relationships and interactions among the Muslims. Islam in China is known as